Determination of organic carbon in mineral and thermal water - Simonič Marjana; International Symposium on Analytical and Environmental Problems (27.) (2021) (Szeged) (University of Szeged Szeged, 2021)
Total organic carbon (TOC) in mineral and thermal waters was measured and statistically evaluated. A calibration curve was constructed, and accuracy and reliability, as well as repeatability and reproducibility, were evaluated in pool waters. The results showed that the method is suitable for the determination of TOC in different thermal and mineral water samples. The results were statistically evaluated. The method was tested within interlaboratory comparison. The measurement deviations were up to 4 %, which ensures the accuracy and reliability of the results.
Keywords: Természettudományok; Kémiai tudományok